Probing new physics with nuclear recoil data from COHERENT - Papoulias, Dimitrios K. (HNPS Advances in Nuclear Physics, 2024)
We exploit the full coherent elastic neutrino-nucleus scattering (CEvNS) dataset reported by the COHERENT Collaboration. In particular, we combine the most recent CsI-2021 measurement with the liquid argon (LAr) measurement from the 2020 campaign. In view of the increased statistics, the refined treatment of quenching effects and the better understanding of the error budget, the present study leads to improved constraints for a set of interactions within and beyond the Standard Model (SM). In terms of a dedicated statistical analysis we provide up-to-date limits on the weak the weak mixing angle and the neutron nuclear radius. With respect to beyond the SM phenomena, we improve previous bounds on electromagnetic neutrino properties and novel light mediator scenarios.